Development of powdered annatto dye - Brocal, Antonietta T. (1982)
This study was done to produce powdered annatto dye from annatto seeds; specifically to determine the optimum extracting conditions for the annatto color and to determine the optimum drying conditions for the extracted dye. The production of powdered annatto dye was divided into two phases. Phase I consisted of the extraction of the dye using three arbitrarily chosen time-temperature combination of steeping water and duration of soaking time. The combination used were 60°C for 10 and 30 minutes, 75°C for 10 and 30 minutes, 90°C fro 10 and 30 minutes. Phase II consisted of the spray drying of the extracted dye using two temperature ranges, 160-180°F and 181-200°F. Results of phase I showed that steeping the raw annatto seeds in a water bath held at 90°C for 30 minutes produce the greatest % weight of dye extracted and absorbance reading. Using the parameters for Phase II it was found out that drying the extract at 181-200°F produce a yellow orange powder with a solubility of 15.00 secs; % moisture content of 10.00; pH of 5.25; % total ash of 10.10; % water-insoluble solids of 13.93 and bulk density of 0.50 g/ml.